(untitled) (Italian Journal of Public Health, 2007)
In 2006 we celebrated the 20th anniversary of the Ottawa Charta for Health Promotion. During these 20 years health promotion became a very influential public health strategy. Let us - with reference to the WHO Health Promotion Glossary - recall some of the core elements of health promotion: “Health promotion represents a comprehensive social and political process, it not only embraces actions directed at strengthening skills and capabilities of individuals, but also actions directed towards changing social, environmental and economic conditions so as to alleviate their impact on public and individual health.Health promotion is the process of enabling people to increase control over the determinants of health and thereby improve their health. Participation is essential to sustain health promotion action.” The Ottawa Charter identifies three basic strategies for health promotion. These are (1) advocacy for health to create the essential conditions for health indicated above; (2) enabling all people to achieve their full health potential; and (3) mediating between different interests in society in the pursuit of health. The Ottawa Charter identifies three basic strategies for health promotion. These are (1) advocacy for health to create the essential conditions for health indicated above; (2) enabling all people to achieve their full health potential; and (3) mediating between different interests in society in the pursuit of health.